If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -3) = -6 + 9 Reorder the terms: -3(-3 + 2x) = -6 + 9 (-3 * -3 + 2x * -3) = -6 + 9 (9 + -6x) = -6 + 9 Combine like terms: -6 + 9 = 3 9 + -6x = 3 Solving 9 + -6x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -6x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 3 + -9 -6x = 3 + -9 Combine like terms: 3 + -9 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 25+9(4x-4)=11(2x-1) | | (x+7)(x+7)(x+7)(x+7)+3=177 | | log((x^2)-6x+9)=0 | | 4x+(2x+6)=24 | | 5x+(x+6)=-30-3x | | 3x+3-5= | | x/5-9=3 | | 4x^2-30x-72=0 | | 2(x+2)-8(6x-6)=18 | | 5x^2-28x=-32 | | 5x^2-28=-32 | | 2(x-2)-8(6x-6)=18 | | 8x-(5x+7)=2 | | 2x-1/3=5 | | 3-4(2m-5)=7 | | 14x^2-25xr-25r^2=0 | | 3x-15=5x+59 | | 0.5s+5=16 | | 5x^2+2x=16 | | 100t^2-1200t+4000=0 | | 4x+3x=-6 | | 5x+3x=-6 | | 2x^2-28x+196=0 | | 2x^2-28x+196=o | | (6c^2-5)-(4c^2+9c+5)= | | -10=5(2w-(-4)) | | 5-2*c-16= | | 8x-15+59=180 | | 10.00-w=1.93 | | 6*c-11+c= | | 2(x-3)-3(x-2)=x+3-(x-1) | | 3x^2+13x=-14 |